EVALUATION OF QUALITY INDICATORS OF LIFE AS A CRITERION OF THE EFFICIENCY OF TREATMENT FOR LIQUIDATORS OF THE ACCIDENT AT CHERNOBYL AEROSPHORUS, PATIENTS WITH HYPERTENSION DISEASE COMORBID WITH GASTROESOPHAGEAL REFLUX DISEASE - Synelnik, V; Oparin, A (Georgian medical news, 2017)
In order to assess the quality of life of liquidators of the accident at the Chernobyl nuclear power plant (CHPP) of patients with hypertensive comorbid disease with gastroesophageal reflux disease, 52 patients aged 46 to 71 years (mean age 57.5±0, 8 years old) who were on inpatient treatment in the therapeutic department of the Regional Clinical Specialized Dispensary for Radiation Protection of the Population of Kharkov from January 2016 to December 2016. The men among the examined were 44 (84.6%), women - 8 (15.4 All patients were divided into 2 groups, Group I patients received standard therapy, Group II patients, in addition to standard therapy, respectively nosology, received additionally the drug Actovegin ® Takeda Austria GmbH. All quality of life indicators were evaluated before the treatment and after In group I patients, after the standard treatment of GB comorbid with GERD, statistically significantly reduced the limitations on the scale of body pain (BP), therefore, in points, on the contrary, to 18.8±2.8 points increased, indicating a decrease in pain after treatment In patients. In patients with group II GB comorbid with GERD after standard treatment with additional use of Actovegin ®, the daily activity limitations associated with the disease on the scales of physical functioning (PF), role activity (RP), physical pain (BP), Vitality (VT), emotional state (RE).